Proceedings of the 5th Universitas Ahmad Dahlan Public Health Conference (UPHEC 2019) 2020
DOI: 10.2991/ahsr.k.200311.001
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic, Knowledge, and Attitude Determinants of Lymphatic Filariasis Medication Adherence in Subang, Indonesia

Abstract: Background: Adherence to lymphatic filariasis (LF) medication during the mass drug administration (MDA) program is an important factor for the success of the LF elimination program. Low adherence rate will likely increase the risk of filariasis transmission in the community. This study was aimed to explore factors associated with medication adherence among populations inSubang, West Java, Indonesia. Method: The researchers analyzed a subset of data obtained from 2017 LF multicenter study in Subang. 676 respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…In Indonesia, for example, drug safety and understanding the importance of MDA for the community were shown to be associated with compliance in two districts [ 44 ]. Other studies have shown that some understanding about LF transmission is important for compliance [ 45 48 ]. Further understanding about how these messages resonate across sex, age groups and regions would help to refine upcoming health information campaigns prior to MDA delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, for example, drug safety and understanding the importance of MDA for the community were shown to be associated with compliance in two districts [ 44 ]. Other studies have shown that some understanding about LF transmission is important for compliance [ 45 48 ]. Further understanding about how these messages resonate across sex, age groups and regions would help to refine upcoming health information campaigns prior to MDA delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Ten and six percent expressed that they got information from Radio and TV respectively about LF in Nigeria [19]. Similarly, one-third (34%) of the respondents stated that the mode of PLOS GLOBAL PUBLIC HEALTH transmission of LF was mosquito bites, and the proportion was higher than our study, and three percent expressed that LF was caused by worms [20].…”
Section: Plos Global Public Healthmentioning
confidence: 45%
“…However, this is in contrast with a study in Indonesia, in which men who worked were aware that filariasis medications could have side effects that could wreak havoc on their health and as a result their finances and were therefore less likely to take antifilariasis medications because they did not want their jobs disturbed [54]. In another study, conducted in Uganda, women were perceived more accepting of drug use [55].…”
Section: Age and Gendermentioning
confidence: 68%